Tocotrienol Berbasis Nabati dalam Akuakultur: Solusi Inovatif untuk Produktivitas, Kesehatan Ikan, dan Keberlanjutan - Wastu Ayu Diamahesa; Fariq Azhar (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Aquaculture plays a pivotal role in global food security but faces challenges such as diseases, oxidative stress, and reliance on unsustainable feed ingredients. Tocotrienol, a plant-based vitamin E isomer, offers an innovative solution with superior antioxidant, anti-inflammatory, and immunomodulatory properties compared to α-tocopherol. This review examines the utilization of tocotrienol from natural sources like red palm oil (Elaeis guineensis) and annatto seeds (Bixa orellana)—containing up to 4,135 mg/L δ-tocotrienol—to enhance aquaculture productivity. Empirical studies demonstrate that tocotrienol supplementation in feed improves Nile tilapia (Oreochromis niloticus) growth and feed efficiency. Its mechanisms involve NF-κB pathway inhibition, Nrf2-ARE activation, and pparγ gene regulation for lipid metabolism. However, challenges such as thermal degradation during feed extrusion and species-specific responses require formulation strategies like nanoencapsulation or industrial byproducts (PFAD). Through integrated approaches, tocotrienol holds potential as a strategic feed additive to advance sustainable aquaculture by enhancing fish health, product quality, and economic efficiency.